Microwave-assisted synthesis of double-shell PtRu/TiO2 catalyst towards methanol electro-oxidation. (7th December 2015) - Hu, Yuming; Zhu, Aimei; Zhang, Chaoli; Zhang, Qiugen; Liu, Qinglin
Abstract: A facile synthetic route was employed to prepare double-shell PtRu/TiO2 catalyst successfully without any stabilizer, in which Ru precursor was reduced by microwave and Pt precursor was in-situ reduced on Ru/TiO2 usingl -ascorbic acid as the soft reductant. The morphology, structure and composition of as-prepared catalysts were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive analysis of X-ray (EDX), transmission electron microscope (TEM) and X-ray photoelectron spectroscopy (XPS). Cyclic voltammetry and chronoamperometry demonstrate the enhancement of electrocatalytic activity and stability towards the methanol electrooxidation of PtRu/TiO2 in comparison with Pt/TiO2, Pt/C (JM) and PtRu/C (JM). Furthermore, the activity for methanol oxidation reaction (MOR) is much higher in alkaline media than that in acidic media. The improved activity and stability could be attributed to the synergetic effects of Pt–Ru and the electrochemically stable TiO2 . Graphical abstract: Highlights: The Ru NPs with narrow size distribution are synthesized by microwave method. Catalyst with double-shell structure is successfully prepared. The PtRu/TiO2 shows high activity and stability for methanol electrooxidation. The electrooxidation performance of PtRu/TiO2 in base is better than that in acid.